MINERALISATION OF METHYL ORANGE BY ELECTRO-FENTON PROCESS USING A POLYPYRROLE/OXIT COMPOSITE CATHODE - Hiền, Nguyễn Thị Lê; Hạnh, Hoàng Thị Mỹ (Vietnam Journal of Science and Technology, 2012)
SUMMARY To promote treatment efficiency, an efficient undivided electrochemical system using a Ppy (Cu1,5Mn1,5O4) composite film on graphite cathode with high production rate of hydrogen peroxide was applied to the electro-Fenton oxidation of a model azo dye, methyl orange (MO). The decrease of MO concentration and treatment efficiency during the electro-Fenton process was investigated by UV-Vis spectra and COD analyses. The results obtained confirme that using the cathode of PPy(Cu1,5Mn1,5O4) allowe treating MO wiht very high efficiency. A solution of 1,53mM MO could be mineralized nearly totally by a electrical charge of 0.08 A.h with a very high current yield.